Traditional games and sports declared as Intangible Cultural Heritage: a legitimate alternative in the case of the Amazonian Peoples of Ecuador/Los juegos y deportes tradicionales declarados como Patrimonio Cultural Inmaterial: alternativa legítima... - Fausto Iván Guapi Guamán (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
In recent years, the practice of traditional games and sports has been losing prominence in society. Therefore, one of the strategies is to convert them into National Intangible Cultural Heritage. The objective of this work was to reflect on the importance of the diverse antecedents on the declaration of Traditional Games and Sports as Intangible Cultural Heritage as a valid alternative to be applicable to the case of the Amazonian peoples of Ecuador. A review of the scientific literature was carried out by means of a bibliographic search of the literature, selection criteria and evaluation of the quality of the selected articles. Traditional games and sports considered intangible cultural heritage contribute to the identity and sense of belonging of the community, region or country. They also have an impact on the tourism sector through the exhibition of recreational and sporting practices. Several countries consider a traditional sport as Intangible Cultural Heritage, as is the case of field hockey in Canada, palín in Chile, pelota in Mexico and Guatemala, Canary Island wrestling, Basque pelota, Valencian pelota and the Aragonese bar toss in Spain, and the fish race in France. In the Ecuadorian context, there are studies that are limited to addressing the concept of traditional games and sports and their typology by region. So far, sporting events have been held at the national level with the aim of promoting the practice of recreational and sporting activities.